Antibodies to henipavirus or henipa-like viruses in domestic pigs in Ghana, West Africa - Hayman DTS; Wang L-F; Barr J; Baker KS; Suu-Ire R; Broder CC; Cunningham AA; Wood JLN (Public Library of Science, 2011)
Henipaviruses, Hendra virus (HeV) and Nipah virus (NiV), have Pteropid bats as their known natural reservoirs. Antibodies against henipaviruses have been found in Eidolon helvum, an old world fruit bat species, and henipavirus-like nucleic acid has been detected in faecal samples from E. helvum in Ghana. The initial outbreak of NiV in Malaysia led to over 265 human encephalitis cases, including 105 deaths, with infected pigs acting as amplifier hosts for NiV during the outbreak. We detected non-neutralizing antibodies against viruses of the genus Henipavirus in approximately 5% of pig sera (N = 97) tested in Ghana, but not in a small sample of other domestic species sampled under a E. helvum roost. Although we did not detect neutralizing antibody, our results suggest prior exposure of the Ghana pig population to henipavirus(es). Because a wide diversity of henipavirus-like nucleic acid sequences have been found in Ghanaian E. helvum, we hypothesise that these pigs might have been infected by henipavirus(es) sufficiently divergent enough from HeVor NiV to produce cross-reactive, but not cross-neutralizing antibodies to HeV or NiV.